2020
DOI: 10.3389/fonc.2020.517061
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Volume and Radiobiological Model-Based Comparative Evaluation of the Gastrointestinal Toxicity Risk of Photon and Proton Irradiation Plans in Localized Pancreatic Cancer Without Distant Metastasis

Abstract: Background: Radiobiological model-based studies of photon-modulated radiotherapy for pancreatic cancer have reported reduced gastrointestinal (GI) toxicity, although the risk is still high. The purpose of this study was to investigate the potential of 3D-passive scattering proton beam therapy (3D-PSPBT) in limiting GI organ at risk (OAR) toxicity in localized pancreatic cancer based on dosimetric data and the normal tissue complication probability (NTCP) model. Methods: The data of 24 pancreatic cancer patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Additionally, Raturi showed that the normal tissue complication probability (NTCP) is not statistically different between photon and proton planning groups. However, these studies did not consider the relationship between the OAR sparing, and the target location since the patient-specific geometry plays a key factor in proton planning ( 15 ). Additionally, the feasibility of proton SBRT-SIB for pancreatic tumor has not been addressed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Raturi showed that the normal tissue complication probability (NTCP) is not statistically different between photon and proton planning groups. However, these studies did not consider the relationship between the OAR sparing, and the target location since the patient-specific geometry plays a key factor in proton planning ( 15 ). Additionally, the feasibility of proton SBRT-SIB for pancreatic tumor has not been addressed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation therapy for abdominal and pelvic tumors is challenging because the small intestine is exquisitely radiosensitive, which limits the dose that can be delivered to tumors without major GI toxicity (2)(3)(4)(5)(6). Unfortunately, there are no FDA-approved therapies to prevent GI radiotoxicities.…”
Section: Discussionmentioning
confidence: 99%
“…This toxicity is especially limiting in the case of abdominal and pelvic cancers, which are surrounded by the exquisitely radiosensitive gastrointestinal (GI) tract, and they require high doses of radiation to achieve tumoricidal effects (2). Multiple studies have highlighted how common GI radiotoxicity is among cancer patients (3)(4)(5). Results from a Phase 3 clinical trial showed that over a third of patients treated with 45 Gy or 50.4 Gy four-field pelvic radiotherapy or pelvic intensitymodulated radiotherapy reported GI symptoms following radiation treatment (6).…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The model parameters used for calculation of pancreatic adenocarcinoma cell death and the NTCP for failure of kidneys, gastric bleeding, striction or fistula of the small intestine and liver failure were given in Appendix 3. [22][23][24][25][26][27][28] Statistical significance was determined applying the paired sample t-test at the 2-tailed, 0.05 significance level.…”
Section: Comparison Metricsmentioning
confidence: 99%
“…The tumor control probability (TCP) and normal tissue complication probability (NTCP) values, proposed according to the Niemierko's effective uniform dose (EUD) model, were calculated using an open‐source MATLAB programme 20,21 . The model parameters used for calculation of pancreatic adenocarcinoma cell death and the NTCP for failure of kidneys, gastric bleeding, striction or fistula of the small intestine and liver failure were given in Appendix 22–28 . Statistical significance was determined applying the paired sample t‐test at the 2‐tailed, 0.05 significance level.…”
Section: Taichib Planningmentioning
confidence: 99%